Breeding sites of the barbastelle Barbastella barbastellus (Schreber, 1774) in Poland ... - Gottfried, Iwona (Zenodo, 2009)
(Uploaded by Plazi for the Bat Literature Project) The paper presents breeding records of the barbastelle (Barbastella barbastellus) from the whole current territory of Poland, both published data from papers and conference abstracts, and unpublished data collected by the authors. Up to 1999, known locations of maternity colonies and sites where young or lactating females had been caught, were assigned to only five forest regions or 16 Universal Transverse Mercator (UTM) squares. The number of such sites has significantly increased since 2000. Breeding sites of barbastelle have now been recorded in all Polish forest regions in 68 UTM squares. Most of the barbastelle sites were located in forest stands with high proportions of beech and oak (65%, N=46), and/or old-growth forest (over 32%, N=23). The highest elevation of a breeding site was at about 500 m.a.s.l. This paper summarises new records of maternity colonies of barbastelles for the first time, as a preliminary step to develop a more comprehensive ...